Evaluasi Kinerja Keuangan Badan Layanan Umum Daerah Kantor Pengelolaan Taman Pintar Yogyakarta Tahun 2011–2015 - Siwi Susanti; Bambang Sugeng Dwiyanto (Universitas Proklamasi 45 Yogyakarta, 2016)
This study aims to determine the financial performance of PPK-BLUDs Management Office Taman Pintar Yogyakarta from the financial aspect using financial ratios, determine the amount of revenue and expenditure performance and determine the amount of the difference between actual revenue and expenditure based financial statements from 2011-2015. Based on the results of this study concluded that the liquidity ratio is very high on the raw value/ideal, it indicates poor management performance because there are many idle funds. Judging from the solvency ratio below the standard value/ideal, so it can be interpreted either as a low solvency ratio has a smaller risk of loss. Judging from the profitability ratio is in the range of sizes of standard value/ideal, so it can be said that the excellent financial performance for the conduct management activities successfully apply the principles of efficiency and productivity. Judging from the achievement of revenue may exceed the planned target indicating that a management plan to be realized with both revenue targets. seen from the achievements of financing showeda good performance, because the management in making budget planning in accordance with the needs, and based on the principles of efficiency and productivity. Judging from the cost recovery rate showed a good performance, because it can cover its costs (cost) income earned (revenue).